Analysis of the Mesoaccessibility of Bus Lines at UFPB: A Case Study in João Pessoa, PB - Llanco, Marcelo Chalub; Silva , Luiz Bueno da; Lima, Jessica Helena de (National Journal of City Management, 2025)
Objective – To analyze the meso-accessibility of bus lines serving the Federal University of Paraíba (UFPB) in João Pessoa, aiming to identify fleet distribution patterns and service quality, with a focus on optimizing urban public transport.Methodology – An innovative approach was used, integrating geospatial data and Bus Service Orders (OSO) analysis, processed using Python programming and specialized libraries (geopandas, folium, branca, scikit-learn, and shapely). Ten bus lines connecting UFPB to the city center and peripheral areas were examined.Originality/Relevance – The study addresses a theoretical gap by applying spatial analysis techniques to assess urban transport meso-accessibility, offers a replicable methodology to identify inefficiencies in mobility systems. The topic is academically relevant due to increasing urbanization and the need for sustainable solutions to problems such as pollution and environmental degradation.Results – The research revealed an uneven distribution of the bus fleet, with some lines significantly overloaded, directly impacting accessibility and service quality.Theoretical/Methodological Contributions – The study contributes an innovative methodological approach, combining geospatial and statistical analysis with Python data processing, allow for the identification of overload patterns and route optimization.Social and Environmental Contributions – The findings can support more effective public policies to improve urban transport, reducing accessibility inequalities and promoting sustainable mobility, with positive impacts on quality of life and the environment.
Keywords: Public transport.; Urban mobility; Geospatial analysis